Geometrical dimensioning and tolerancing for design, manufacturing and inspection : a handbook for geometrical product specification using ISO and ASME standards - Henzold, G. (Butterworth-Heinemann, 2021)
Geometrical Dimensioning and Tolerancing for Design, Manufacturing and Inspection: A Handbook for Geometrical Product Specification Using ISO and ASME Standards, Third Edition presents the state-of-the art in geometrical dimensioning and tolerancing. The book describes the international standardization in this field while also indicating how it differs from the American Standard ASME Y14.5M. The general principles of geometric dimensioning and tolerancing are described, helping users define precision-related specifications unambiguously and consistently with the constraints of the manufacturing and inspection processes. Principles for the inspection of geometrical deviations are given, along with a basis for tolerancing suitable for inspection. Since publication of the second edition of this book in 2006 more than ten ISO GPS standards have been revised, involving the introduction of new symbols and concepts, and in many cases default interpretation of the tolerance indicators have changed, in addition two new versions of American standard ASME Y14.5 (2009 and 2018) have appeared. This book is an ideal introduction to geometrical dimensioning and tolerancing for students, and an essential reference for researchers and practitioners in the fields of design, manufacturing and inspection.